2004
DOI: 10.1210/jc.2003-030934
|View full text |Cite
|
Sign up to set email alerts
|

The Hormonal Phenotype of Nonclassic 3β-Hydroxysteroid Dehydrogenase (HSD3B) Deficiency in Hyperandrogenic Females Is Associated with Insulin-Resistant Polycystic Ovary Syndrome and Is Not a Variant of Inherited HSD3B2 Deficiency

Abstract: To test our hypothesis that the hormonal phenotype of mild 3beta-hydroxysteroid dehydrogenase (HSD3B) deficiency in hyperandrogenic females (HF) is related to insulin-resistant polycystic ovary syndrome (PCOS), we compared insulin sensitivity and gonadotropin secretion in HF with compromised ( downward arrow ) adrenal HSD3B phenotype despite normal HSD3B2 genes (n = 6) to those in HF with classic PCOS (n = 9) of similar ages (14-36 yr). The same was examined in premature pubarche (PP) girls with (n = 4) and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 45 publications
2
16
0
2
Order By: Relevance
“…Ambroziak et al reported that adult patients with classical 21-hydroxylase deficiency have obesity, hyperinsulinemia, insulin resistance, and hyperleptinemia more frequently than age/sex matched controls (Ambroziak et al, 2010). Carbunaru et al have reported that the hormonal phenotype of non-classic 3--ol dehydrogenase deficiency in hyperandrogenemic females is associated with insulin-resistant PCOS and is not a variant of genetic HSD3B2 deficiency (Carbunaru et al, 2004). This article is consistent with a publication by (Lutfallah et al, 2002) that proposed new hormonal criteria for the diagnosis of those patients with mutations in the Type II 3-beta-ol dehydrogenase exon.…”
Section: Non-classical 21-hydroxylase Deficiencysupporting
confidence: 79%
See 1 more Smart Citation
“…Ambroziak et al reported that adult patients with classical 21-hydroxylase deficiency have obesity, hyperinsulinemia, insulin resistance, and hyperleptinemia more frequently than age/sex matched controls (Ambroziak et al, 2010). Carbunaru et al have reported that the hormonal phenotype of non-classic 3--ol dehydrogenase deficiency in hyperandrogenemic females is associated with insulin-resistant PCOS and is not a variant of genetic HSD3B2 deficiency (Carbunaru et al, 2004). This article is consistent with a publication by (Lutfallah et al, 2002) that proposed new hormonal criteria for the diagnosis of those patients with mutations in the Type II 3-beta-ol dehydrogenase exon.…”
Section: Non-classical 21-hydroxylase Deficiencysupporting
confidence: 79%
“…Gene therapy, wherein the defective gene is supplemented with a functional one should, theoretically, be the ideal therapy for every form of CAH, with the possible exception of non-classical 3--ol dehydrogenase deficiency, for which no mutation in the exon has been identified (Carbunaru et al, 2004).…”
Section: Gene Therapymentioning
confidence: 99%
“…However, in patients who develop this form of hyperandrogenism during adult life, no specific genetic defect has been detected, and it has been suggested that these patients may have a functional enzymatic deficiency (143,144). In practice, these patients may be considered affected by PCOS because they generally have anovulation and menstrual irregularities and have similar phenotypic features, including insulin resistance and LH hypersecretion, as patients of classic PCOS (142,144).…”
Section: Hyperandrogenemiamentioning
confidence: 99%
“…Circulating DHEAS levels are positively, albeit weakly, associated with the degree of hypersecretion. The adrenocortical dysfunction observed does not appear to be the result of genetic defects affecting 21-OH (P450c21, encoded by CYP21) [49,50], 11β-hydroxylase (11-OH; P450c11, encoded by CYP11B1) [51], or 3β-hydroxysteroid dehydrogenase (3β-HSD, encoded by HSD3B2) [52,53]. In fact, the single steroidogenic difference observed between PCOS women and healthy controls appears to be a greater estimated Δ 5 17-OH activity [50], primarily observed in PCOS patients with high DHEAS levels [43].…”
Section: B) Abnormalities Of Adrenocortical Biosynthesis In Pcosmentioning
confidence: 99%